Interacting effects of insect and ungulate herbivory on Scots pine growth - Nordkvist, Michelle (Sci Rep, 2020)
Most plants are subjected to damage from multiple species of herbivores, and the combined impact on plant growth can be non-additive. Since plant response to herbivores tends to be species specific, and change with repeated damage, the outcome likely depend on the sequence and number of attacks. There is a high likelihood of non-additive effects on plant growth by damage from mammals and insects, as mammalian herbivory can alter insect herbivore damage levels, yet few studies have explored this. We report the growth response of young Scots pine trees to sequential mammal and insect herbivory, varying the sequence and number of damage events, using an ungulate-pine-sawfly system. Combined sawfly and ungulate herbivory had both additive and non-additive effects on pine growth—the growth response depended on the combination of ungulate browsing and sawfly defoliation (significant interaction effect). Repeated sawfly herbivory reduced growth (compared to single defoliation) on un-browsed trees. However, on browsed trees, depending on when sawfly defoliation was combined with browsing, trees exposed to repeated sawfly herbivory had both higher, lower and the same growth as trees exposed to a single defoliation event. We conclude that the sequence of attacks by multiple herbivores determine plant growth response.